Developing competency models to promote integrated human resource practices - Rodriguez, Donna; Patel, Rita; Bright, Andrea; Gregory, Donna; Gowing, Marilyn K. (Human Resource Management, 2002)
AbstractToday, competencies are used in many facets of human resource management, ranging from individual selection, development, and performance management to organizational strategic planning. By incorporating competencies into job analysis methodologies, the Office of Personnel Management (OPM) has developed robust competency models that can form the foundation for each of these initiatives. OPM has placed these models into automated systems to ensure access for employees, human resources professionals, and managers. Shared access to the data creates a shared frame of reference and a common language of competencies that have provided the basis for competency applications in public sector agencies. © 2002 Wiley Periodicals, Inc.